Buckling Analysis of Rectangular Plates with Variable Thickness Resting on Elastic Foundation. (30th January 2015) - Viswanathan, K K; Navaneethakrishnan, P V; Aziz, Z A
Abstract: Buckling of rectangular plates of variable thickness resting in elastic foundation is analysed using a quintic spline approximation technique. The thickness of the plate varies in the direction of one edge and the variations are assumed to be linear, exponential and sinusoidal. The plate is subjected to in plane load of two opposite edges. The buckling load and the mode shapes of buckling are computed from the eigenvalue problem that arises. Detailed parametric studies are made with different boundary conditions and the results are presented through the diagram and discussed.